The road to February 1948. Theses for research on contemporary history - Brenner, Christiane (Dějiny – teorie – kritika, 2006)
The article deals with the theoretical and methodological background of research on the history of Czechoslovakia in 1945-1948. The author comes to terms with the generally shared interpretive framework of research, i.e. the image of the struggle between democracy and emerging totalitarianism, and systematically shows why this interpretive model is inaccurate and thus leads to biased conclusions. She argues that in the future, scholars should avoid methodological errors consisting in excessive personification of the topic. In contrast, the author focuses her attention on the profound political, economic, social and value changes that took place in post-war Czechoslovakia, and sees them not just as the pure consequences of the war and the trauma of Munich, but as part of a broader and more complex process of transformation. Symptoms of this process were already visible in the first Czechoslovak Republic, fully developed in the short period of the Second Republic, were still evident during the war, and continued after 1945 and 1948. Thus, we encounter trends that persisted despite the rise of externally quite different regimes. For the period 1945-1948, then, the democracy-totalitarianism dichotomy loses its meaning under this perspective, and instead becomes more important to understand the shift in understanding of democracy and political power, the call for a new order, the socialist concept, the nature of politics, and questions of continuity with the pre-war republic.